If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+6=-8x+5
We move all terms to the left:
3x+6-(-8x+5)=0
We get rid of parentheses
3x+8x-5+6=0
We add all the numbers together, and all the variables
11x+1=0
We move all terms containing x to the left, all other terms to the right
11x=-1
x=-1/11
x=-1/11
| 3/8=u/12 | | 10x37=3x+5 | | 8x-38=4x6 | | x^2+2x-24=180 | | 2/3=c/18 | | (6x+4)=(5x+6) | | 4(w+3)=2(w+30.5) | | 3(n+2)+3n=28.5 | | 3(y+3)=2(2y+4) | | 2/5+n=25 | | 14+9x=101 | | x^2=35.84 | | D-4d-6d-8=2d | | (4.5y-12)=9 | | j/2+2=3 | | 13x.5=11x-11 | | -3.2-u/4=u | | F(x)=5x-60 | | 5(y-4)=8y-23 | | (2n+1)^2/4=4n^2+4n+1 | | 10x+-3=-33 | | 2v^2+9v-110=0 | | 4-8w=52 | | 10m+4=-16 | | 4/49x+12/49=8/49 | | d2–2d–24=0 | | 5x=1/35 | | Y=x/2+20 | | (2m-3)(m-8)=0 | | (4m-7)(m-3)=0 | | 2/31x+10/31=6/31 | | 2(b-3)=18 |